Manajemen Kesiswaan dalam Membentuk Budaya Religius di MTs. S Teupah Barat - Yunita Gibon (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2024)
This research examines how the management of implementing religious culture can be realized in building a neat and structured culture at various levels of education, especially at MTs. S Teupah Barat. The aim of this research is to find out how students plan to form a religious culture at Madrasah Tsanawiyah Suwasta Teupah Barat, to find out how students organize religious cultural activities at Madrasah Tsanawiyah Suwasta Teupah Barat. find out how students carry out activities in forming religious culture at Madrasah Tsanawiyah Suwasta Teupah Barat. The research results, (1) Planning in forming a religious culture from the family and community environment, schools also have a very important role in forming religious culture, although not significantly. (2) Implementation of religious culture, namely: a. Dhuha prayer in congregation, b. Congregational midday prayer, c. Friday prayers, d. Recitations of the Qur'an, e. implementation of 5S (Smile, Greeting, Greeting, Polite and Courteous (3) Religious cultural activities that are formed through a long and tiring process. There are many violations that still occur, which is not an obstacle for the head of the Madrasah and his staff to improve the intelligent life of the nation more motivation and encouragement to keep going.